Ergonomics of an art studio: methodology for comfortable and productive creativity - Sadykova , Zhanna; Almasbayeva , Aisulu (Рroblems of engineering and professional education, 2024)
This article discusses the importance of applying ergonomic principles in the art studio. An art studio is a space designed to facilitate creativity, allowing artists to express themselves freely while maintaining a productive and comfortable work environment. The ergonomics of an art studio plays a crucial role in ensuring the efficiency and well-being of artists by addressing key factors such as workspace arrangement, lighting, temperature, humidity, and ergonomic tools. Proper workspace organization, including adjustable chairs, well-positioned desks, and accessible storage, contributes to reducing physical strain and increasing productivity. Adequate lighting is essential to provide accurate color perception and minimize eye fatigue, while optimal temperature and humidity levels ensure comfort during prolonged work sessions. Additionally, the use of ergonomic tools, such as specially designed brushes and drawing supports, enhances the creative process by reducing strain on the hands and wrists. Furthermore, noise control, ventilation, and proper material storage play significant roles in maintaining a healthy and inspiring environment. Regular breaks and physical exercises help mitigate the negative effects of prolonged sitting and repetitive movements. The research highlights the importance of implementing ergonomic principles in art studios to enhance artistic performance, improve health conditions, and create a sustainable working environment. By prioritizing ergonomics, artists can maximize their creative potential while preserving their physical and mental well-being.